2015
DOI: 10.1152/ajpheart.00499.2014
|View full text |Cite
|
Sign up to set email alerts
|

Aquaporin-1 facilitates pressure-driven water flow across the aortic endothelium

Abstract: Aquaporin-1, a ubiquitous water channel membrane protein, is a major contributor to cell membrane osmotic water permeability. Arteries are the physiological system where hydrostatic dominates osmotic pressure differences. In the present study, we show that the walls of large conduit arteries constitute the first example where hydrostatic pressure drives aquaporin-1-mediated transcellular/transendothelial flow. We studied cultured aortic endothelial cell monolayers and excised whole aortas of male Sprague-Dawle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
54
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(56 citation statements)
references
References 70 publications
2
54
0
Order By: Relevance
“…In the endothelial layer of these arteries, AQP1 sets the critical transmural pressure for subendothelial intima compression (Nguyen et al . ) and may regulate solute advection like low‐density lipoprotein cholesterol (LDL) (Tedgui & Lever ). LDL entry to the subendothelial intima layer is one of the early steps in atherogenesis (Simionescu et al .…”
Section: Discussionmentioning
confidence: 99%
“…In the endothelial layer of these arteries, AQP1 sets the critical transmural pressure for subendothelial intima compression (Nguyen et al . ) and may regulate solute advection like low‐density lipoprotein cholesterol (LDL) (Tedgui & Lever ). LDL entry to the subendothelial intima layer is one of the early steps in atherogenesis (Simionescu et al .…”
Section: Discussionmentioning
confidence: 99%
“…Many have suggested that the major barrier to water permeability is the endothelial cell (EC) layer based on the effect of gross mechanical disruption of these cells (1,10,12). Recent data have shown that inhibition of AQP1, highly expressed in vascular EC (13), has little impact on the measured water permeability at physiological pressures (14), suggesting that AQP1-facilitated water transport across the endothelium is not rate limiting. In this study we characterize the distribution of permeability and the associated pressure profile across the wall, in in vitro intact pressurized rat mesenteric arteries.…”
mentioning
confidence: 99%
“…Further studies are required to determine the effect of GDNF and other mitogens such as basic fibroblast growth factor, transforming growth factor-β, vascular endothelial growth factor and hydrocortisone on BNB water flux. It is currently unknown whether hydraulic conductivity at the BNB or BBB is facilitated by specific water channels (such as aquaporin 1) (Nguyen et al, 2015) providing a transcellular route of entry or via transcellular or paracellular osmosis. In future studies, gene knock-down could be employed to manipulate tight junction, transporter, and ionic/water channel protein levels using pHEndECs or THEndECs, or THBMECs to gain insights to their roles in BNB and BBB hydraulic conductivity respectively.…”
Section: Discussionmentioning
confidence: 99%